2018
DOI: 10.1002/asjc.1736
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Quantized Synchronization for Chaotic Neural Networks with Successive Packet Dropouts

Abstract: In this paper, the problem of uniform quantized synchronization is investigated for chaotic neural networks with packet dropouts. By means of the stochastic analysis approach and inequality technique, sufficient conditions are derived under which the synchronization error system is exponentially ultimately bounded in mean square. Finally, a numerical example is provided to validate the feasibility and effectiveness of the proposed results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Consequently, this paper studies the influence of multi‐channel fading and hybrid cyber attacks on the NCSs, which is more general. In addition, when the multi‐channel fading degenerates into random packet dropout phenomenon [44], it is similar to DoS attack. So this paper considers the mixture of deception attack and replay attack.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Consequently, this paper studies the influence of multi‐channel fading and hybrid cyber attacks on the NCSs, which is more general. In addition, when the multi‐channel fading degenerates into random packet dropout phenomenon [44], it is similar to DoS attack. So this paper considers the mixture of deception attack and replay attack.…”
Section: Problem Formulationmentioning
confidence: 99%
“…where w ∈ R . It should be noted that although (18) is continuous everywhere, it is not differentiable at the discontinuous points of the quantizer. As a result, by using the generalized gradient defined in [25], we will obtain:…”
Section: Lemma 3 ([16]) Suppose a Qmentioning
confidence: 99%
“…In [14] the authors tried to find the bound of quantization error for a system with first‐order discrete‐time agents. Moreover, in [18], the authors attempted to solve the synchronization problem of chaotic neural networks using quantized information. They showed that the synchronization error could be exponentially ultimately bounded in mean square criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an adaptive synchronization for general complex networks with uncertainties was introduced in [9]. Further, synchronization of chaotic neural networks by means of stochastic analysis and inequality technique was presented in [10]. An adaptive fuzzy output feedback synchronization of non‐linear multi‐agent systems with input saturation was dealt in [11].…”
Section: Introductionmentioning
confidence: 99%